2004
DOI: 10.3189/172756404781814212
|View full text |Cite
|
Sign up to set email alerts
|

Variations of glacier frontal positions on the northern Antarctic Peninsula

Abstract: Changes in the ice fronts on the Antarctic Peninsula north of 70˚S are currently being investigated through a comprehensive analysis of Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) and Landsat Thematic Mapper (TM) data as part of the international research initiative 'Global land Ice Measurements from Space' (GLIMS). Regional case studies are presented that cover a variety of glacial systems distributed over the northern Antarctic Peninsula and provide data on glacier front variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 21 publications
1
40
0
3
Order By: Relevance
“…Higher atmospheric and oceanic temperatures have also contributed to the retreat during the past half-century of marine glacier fronts along the western coast of the AP, north of $708 S (Cook and others, 2005). An overall trend of retreating ice fronts has also been observed in studies analysing both marine-and land-terminating glaciers in the region (Rau and others, 2004), though the latter has shown a range of different glacier variations throughout the study area over the period analysed (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), including stationary ice fronts on the northwestern coast of the AP. A widespread acceleration trend of glaciers on the AP west coast has been observed from repeated flow rate measurements during 1992-2005 and attributed to a dynamic response to frontal thinning (Pritchard and Vaughan, 2007).…”
Section: Introductionmentioning
confidence: 76%
“…Higher atmospheric and oceanic temperatures have also contributed to the retreat during the past half-century of marine glacier fronts along the western coast of the AP, north of $708 S (Cook and others, 2005). An overall trend of retreating ice fronts has also been observed in studies analysing both marine-and land-terminating glaciers in the region (Rau and others, 2004), though the latter has shown a range of different glacier variations throughout the study area over the period analysed (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), including stationary ice fronts on the northwestern coast of the AP. A widespread acceleration trend of glaciers on the AP west coast has been observed from repeated flow rate measurements during 1992-2005 and attributed to a dynamic response to frontal thinning (Pritchard and Vaughan, 2007).…”
Section: Introductionmentioning
confidence: 76%
“…Additionally, atmospheric warming, together with warmer ocean temperatures, have been pointed out as drivers, through different physical processes, of the disintegration of some ice shelves on the northeastern coast of the AP (MacAyeal et al, 2003;Shepherd et al, 2003;van den Broeke, 2005;Cook and Vaughan, 2010), with subsequent acceleration of the inland glaciers feeding the ice shelves (Rott et al, 1996;Rignot et al, 2004;Scambos et al, 2004), and also of the widespread retreat of marine glacier fronts of the AP over the past halfcentury (Cook et al, 2005). An overall tendency of retreating ice fronts has also been observed in studies analysing, over the period 1986-2002, both marine-terminating and landterminating glaciers in the region (Rau et al, 2004). A widespread acceleration trend of glaciers on the AP west coast has been observed as well from repeated flow rate measurements within [1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005], and attributed to a dynamic response to frontal thinning (Pritchard and Vaughan, 2007).…”
Section: Introductionmentioning
confidence: 80%
“…Skvarca and others (1995) identified greatly reduced glacier extent for the period 1975-93, and the subsequent remote-sensing study by Rau and others (2004) showed that of five land-terminating glaciers on the Ulu Peninsula, only one displayed indications of glacier recession between 1975 and 1988.…”
Section: Study Site and Glacial Historymentioning
confidence: 97%